Influence of Paclitaxel and Heparin on vitality, proliferation and cytokine production of endometrial cancer cells - Dinkic, Christine; Schütz, Florian; Brucker, Janina; Rom, Joachim; Sohn, Christof; Fluhr, Herbert (Geburtshilfe und Frauenheilkunde, 2017)
Methods This study investigated the effect of paclitaxel (PTX) combined with heparins on the vitality of endometrial cancer cells using viability and cytotoxicity assays. The study also examined whether treatment with paclitaxel and heparin influences cytokine secretion or expression. Results Heparin treatment did not influence cell viability, and no influence of heparins in combination with paclitaxel was seen for the evaluated cancer cell lines HEC-1-A, KLE, RL 95-2 and AN3-CA compared to untreated cells. Secretion of the cytokines CCL5, CCL2 and IL-6 increased after paclitaxel treatment in several endometrial cancer cell lines, but no general effect on cytokine secretion was detected after heparin treatment. A significant decrease in CCL5 expression was only detected in KLE cells following treatment with heparin and paclitaxel, and an increase in the expression of CCL5 in RL 95-2 cells. Conclusion Further in-depth studies are needed to investigate the functions of cytokines CCL2, CCL5 and IL-6 in endometrial cancer cells treated with paclitaxel. Although no general effect on cytokine secretion was detected following heparin treatment, a selective modulatory impact could exist.